Reduced sB7-H3 Expression in the Peripheral Blood of Systemic Lupus Erythematosus Patients - Jing Sun; Huijun Lai; Dong Shen; Pingping Wu; Jie Yang; Zhongwen Sun; Yundi Guo (Journal of Immunology Research)
Both membrane-bound and soluble forms of costimulatory molecules play important roles in immune-regulatory networks. B7-H3, a member of the B7 family, has been found with aberrant expression in tumors and infectious disease. However, the significance of sB7-H3 expression in systemic lupus erythematosus (SLE) has not been investigated. Using the peripheral blood of 78 SLE patients, we established a comprehensive database containing clinical data and relevant laboratory tests. We found that sB7-H3 expression in SLE patients was significantly lower compared with the healthy individuals. In addition, sB7-H3 levels in the patients were positively correlated with the disease activity as indicated by SLE disease activity index score, rashes, fever, and inflammatory cytokines. Moreover, sB7-H3 was associated with the counts of red blood cells and hemoglobin. Our findings suggest that sB7-H3 might counteract the aberrant immune response and potentially serve as a monitoring indicator of disease progression and therapeutic target in SLE treatment.